Alocação de equipes e desenvolvimento do cronograma em projetos de software utilizando otimização - Felipe Colares Torres (2010)
In software management, planning is recognized as a key aspect to the success. Project scheduling, which includes assigning responsibilities and developing the schedule, is an activity as much important as complex. Ad hoc approaches have many negative points, most of them due the development becoming dependent of individuals rather than the process. Based on this, the present work deals with the problem by using computational optimization techniques to overcome current limitations by presenting an automated approach. Applying optimization techniques to software engineering problems is a recent paradigm that has received growing attention by the academic community, leading to a new field called Search-Based Software Engineering (SBSE). This work presents an approach based on multi-objective optimization, both proposing a new formulation to the problem and presenting an algorithm to solve it. Tests and experiments validate the proposed approach and demonstrate its efficacy and applicability.